URGENSI TASAWUF DI MASA KINI - Abubakar (STAI YAPIS Takalar, 2021)
Abstract In the present, which is also known as the contemporary and modern times, spiritual morals are in the spotlight. Various problems often arise related to this spiritual moral, including the erosion of positive spiritual moral values ??caused by the culture of materialism and hedonism. This problem arises not only among mankind in general, but also among Muslims in particular. For such conditions, humans look for alternatives as a way out of dependence on materialistic and hedonistic cultures. One of them is Sufism. The teachings of Sufism whose origins grew from the pattern of life that had been exemplified by the Prophet Muhammad. and his friends. The core of his teaching is the improvement of morals/morals which includes both physical and mental. To get a commendable spiritual moral, requires a serious and continuous struggle, which is managed by an approach of introspection, repentance, dhikr, tafakkur, zuhud, and all forms arranged in the order of Sufism, all of which are tied to takhalli, tahalli and tajalli. Sufism based on zuhudan as practiced by the Prophet Muhammad. and most of the friends and tabi'in, are the implementation of the values ??of the Qur'an and the hadith of the Prophet Muhammad. which is oriented towards the hereafter and strives to distance oneself from excessive worldly confines and aims to purify oneself, relying on Allah swt. very relevant and very important in providing solutions to human problems today.